Pengaruh Budaya Keselamatan dan Kesehatan Kerja (K3) Terhadap Unsafe Action Pekerja di PT. Azima Rakan Jaya: Penelitian - Nur Amalia; Ivana Wardani; Cut Saura Salmira (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A project is a collection of activities intended to achieve a specific end result that is of significant importance to management. One such project is a construction project. The construction process is generally characterized by numerous hazards. One of the focuses of contractors is creating favorable Occupational Safety and Health (OHS) conditions on the project. Meanwhile, an Occupational Safety and Health (OHS) culture among workers plays a crucial role in shaping their attitudes toward occupational safety and health. This research was conducted to identify and analyze factors influencing occupational safety and health culture, particularly in construction projects, and to analyze the influence of these factors on construction project performance.